Testing the feasibility of a mobile technology intervention promoting healthy gestational weight gain in pregnant women (txt4two) - study protocol for a randomised controlled trial - Willcox, Jane Catherine (Trials, 2015)
BACKGROUND: Overweight, obesity and excess gestational weight gain (GWG) are associated with negative health outcomes for mother and child in pregnancy and across the life course. Interventions promoting GWG within guidelines report mixed results. Most are time and cost intensive, which limits scalability. Mobile technologies (mHealth) offer low cost, ready access and individually-tailored support. We aim to test the feasibility of an mHealth intervention promoting healthy nutrition, physical activity and GWG in women who begin pregnancy overweight or obese. METHODS/DESIGN: txt4two is a parallel randomised control trial pilot recruiting women with a singleton, live gestation between 10(+0) and 17(+6) weeks at the first hospital antenatal clinic visit. Inclusion criteria are pre-pregnancy BMI > 25 kg/m(2) and mobile phone ownership. One hundred consenting women will be randomised to intervention or control groups at a 1:1 ratio. All participants will receive standard antenatal care. In addition, the txt4two intervention will be delivered from baseline to 36 weeks gestation and consists of a tailored suite of theoretically-grounded, evidence-based intervention strategies focusing on healthy nutrition, physical activity and GWG. This includes: mobile phone interactive text messages promoting positive health behaviours, goal setting and self-monitoring; video messages; an information website; and a private moderated Facebook® chat forum. The primary outcome is the feasibility of the intervention. Secondary outcomes include GWG and participants’ knowledge and behaviour regarding diet and physical activity during pregnancy. DISCUSSION: Findings will inform the development of larger-scale mHealth programmes to improve the delivery of healthy pregnancy nutrition, physical activity and GWG, that could be widely translated and disseminated. TRIAL REGISTRATION: Australian New Zealand Clinical Trials Registry: ACTRNU111111544397. Date of registration: 19 March 2014. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13063-015-0730-1) contains supplementary material, which is available to authorized users.